ENT 530 : Case Study: Bake by Anna / Azyla Zulkhairi ... [et al.] - Zulkhairi, Azyla; Shaheezam, Yasmin Azra; Ramly, Muhammad Izdihar Fadhli; Ahmad Ikhwan, Ahmad Aiman; Che Nordin, Muhamad Aizat Afiq (2021)
The case study is focusing on the ability for the SME’s to sustain and maintain the business in reality as it will affect their company cash flow and as well as our economy growth. The strength of SMEs is determined by how the business owner plans to carry out their duties in order to save the company. SMEs business owners usually tend to struggle a lot to survive in their respective industries due to lack of certain field in their business. There have been a few challenges in operating the company Bake by Anna, and this case study is focusing on identifying the business’s major problems and solutions to assist the business owner in encountering the harsh industry reality. The case study findings are based on an online interview conducted with Mrs. Anis Zulaikha, one of the managers, to obtain more information about her company. Furthermore, this case study is also focused on what are the strengths, weaknesses, opportunities and threats of this business. It helps the business make the most of what they have to offer their organization. The most important thing is that it could reduce the risk of failure by recognizing where the businesses are lacking at and removing hazards that would otherwise catch them off guard. In conclusion, this case study of Bake by Anna is designed to assess the business owner's resilience in the face of hardship and the ability to survive in the face of any challenges they might face from now onwards. This case study summarizes the impact on SMEs in certain field as SMEs have always been the toughest to maintain their business due to certain part that they lack off.